Power station boiler water wall high temperature stress corrosion test method

CN122921808APending Publication Date: 2026-10-16JIANGSU GUOXIN JINGJIANG POWER GENERATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611419215.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]在现有技术中,现有电站锅炉水冷壁管材高温应力腐蚀试验方法通常依赖外部约束装置或专用加载设备对试样施加应力,存在试验设备复杂、成本较高、应力加载方式与实际水冷壁管热失配应力状态不一致等问题,同时现有方法难以在高温腐蚀环境下实现应力水平的连续调节,且单次试验通常只能模拟单一应力条件,无法满足水冷壁管在不同应力状态下的对比试验需求;

Benefits of technology

1、本发明首先依据材料试验数据对高温应力腐蚀试验的第二测试材料对应第二板厚进行设置,而后对通过第一测试材料和第二测试材料制备得到的测试样板进行退火处理,并判断退火处理完成的测试样板是否存在缺陷,实现对测试样板是否存在缺陷的预先筛除,提升后续试验数据的可靠性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122921808A_ABST
    Figure CN122921808A_ABST
Patent Text Reader

Abstract

The application discloses a kind of power station boiler water-cooled wall high temperature stress corrosion test methods, it is related to metal material high temperature corrosion test technical field, solve the problem that existing technology is through high temperature stress corrosion test to water-cooled wall pipe material by high temperature rigid clamp, high temperature rigid clamp is easy to corrode degradation, method specifically is: according to the second plate thickness of the second test material of high temperature stress corrosion test is set according to material test data;Annealing treatment is carried out to the test sample prepared by first test material and second test material, it is judged whether the test sample that annealing treatment is completed exists defect;Test sample is heated test by the synthetic coal ash prepared, and then it is judged whether the test sample after heating test occurs high temperature stress corrosion cracking, the application realizes using thermal expansion coefficient mismatch to generate thermal stress to water-cooled wall pipe material high temperature stress corrosion test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-temperature corrosion testing technology for metallic materials, specifically a high-temperature stress corrosion testing method for water-cooled walls of power plant boilers. Background Technology

[0002] Water-cooled walls in power plant boilers are heat-receiving surface structures installed on the inner walls around the boiler furnace. They are typically formed by welding multiple water-cooled wall tubes and fins together. They absorb the radiant heat generated by fuel combustion in the furnace and transfer this heat to the working fluid flowing inside the tubes, achieving water heating, evaporation, and cooling and protection of the furnace walls. As an important component of the boiler's steam-water circulation system, the outer side of the water-cooled wall tubes directly contacts the high-temperature flue gas environment of the furnace, while the inner side carries the steam-water medium, maintaining the boiler's thermal energy conversion process through continuous heat exchange.

[0003] In the existing technology, the existing high-temperature stress corrosion test method for water-cooled wall tubes of power plant boilers usually relies on external constraint devices or special loading equipment to apply stress to the sample. This has problems such as complex test equipment, high cost, and inconsistency between the stress loading method and the actual thermal mismatch stress state of the water-cooled wall tube. At the same time, the existing method is difficult to achieve continuous adjustment of stress level in high-temperature corrosion environment, and a single test can usually only simulate a single stress condition, which cannot meet the comparative test requirements of water-cooled wall tubes under different stress states. Therefore, this invention proposes a method for testing high-temperature stress corrosion of water-cooled walls in power plant boilers. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the purpose of this invention is to provide a method for testing high-temperature stress corrosion of water-cooled walls in power plant boilers.

[0005] The technical problem to be solved by this invention is: How to achieve controllable simulation of high-temperature stress corrosion of water-cooled wall pipes.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers, the method comprising: Step S100: Set the second plate thickness corresponding to the second test material for the high-temperature stress corrosion test based on the material test data; Step S200: Anneal the test sample prepared by the first test material and the second test material, and then determine whether there are defects in the annealed test sample. In step S300, the test sample is heated using the prepared synthetic coal ash, and then it is determined whether the test sample has undergone high-temperature stress corrosion cracking after the heating test.

[0007] Furthermore, the first test material was low-alloy heat-resistant steel water-cooled wall pipe, and the second test material was austenitic heat-resistant steel.

[0008] Furthermore, the material test data are the first linear expansion coefficient and first elastic modulus of the first test material at the target test temperature, and the second linear expansion coefficient and second elastic modulus of the second test material.

[0009] Further, step S100 includes the following sub-steps: Step S101: Obtain the target test temperature for the high-temperature stress corrosion test on the first test material, and at the same time obtain the ambient temperature of the test environment of the first test material and the second test material. Subtract the ambient temperature from the target test temperature to calculate the heating temperature difference of the high-temperature stress corrosion test. Step S102: Obtain the first linear expansion coefficient of the first test material and the second linear expansion coefficient of the second test material; subtract the first linear expansion coefficient from the second linear expansion coefficient to calculate the difference in linear expansion coefficients between the first test material and the second test material. Step S103: Obtain the first plate thickness and first elastic modulus of the first test material, and the second elastic modulus of the second test material; Step S104: Calculate the thickness of the second plate based on the equilibrium equation of the first and second test materials during heating in the high-temperature stress corrosion test.

[0010] Furthermore, the calculation process for the second plate thickness is as follows: During the heating process in the high-temperature stress corrosion test, the first test material and the second test material are in equilibrium and satisfy the equilibrium equation. The tensile stress of the first test material is derived based on the equilibrium equation. The second plate thickness of the second test material is calculated by substituting the preset tensile stress corresponding to the first test material in the high-temperature stress corrosion test into the tensile stress calculation formula.

[0011] Further, step S200 includes the following sub-steps: Step S201: Prepare two pieces of first test material with a first plate thickness and one piece of second test material with a second plate thickness; Step S202: The first test material and the second test material are stacked and placed according to the fixed stacking method, and the first test material and the second test material are welded to obtain a test sample for high temperature stress corrosion test. Step S203: Heat the test sample to the annealing temperature and hold it at that temperature for a fixed time, then cool the test sample to the ambient temperature to obtain the annealed test sample.

[0012] Furthermore, step S200 also includes the following sub-steps: Step S204: Heat the test sample to the target test temperature using a heating device, maintain the temperature for a fixed time, and then cool the test sample to the ambient temperature. Step S205: Repeat step S204 a fixed number of times to cycle-heat the test sample, and then analyze and detect whether there are defects in the test sample, and obtain the ultrasonic signal amplitude. When the amplitude of any ultrasonic signal is greater than or equal to a preset threshold, it is determined that the test sample has a defect. Steps S201 to S204 are repeated to prepare the test sample again until the test sample has no defects, then proceed to step S300. When the amplitude of all ultrasonic signals is less than the preset threshold, the test sample is deemed qualified and proceeds to step S300.

[0013] Furthermore, the detection process of the ultrasonic signal amplitude is as follows: Clean the surface of the test sample; Move the ultrasonic probe sequentially along the weld end - rounded corner transition area - effective test area - rounded corner transition area - weld end; Record the amplitude of the ultrasonic signal obtained by the ultrasonic probe.

[0014] Further, step S300 includes the following sub-steps: Step S301: Prepare synthetic coal ash according to the preset mass fraction of chemical reagents, and then drop the test solution into the synthetic coal ash to obtain a paste-like corrosive medium; Step S302: Apply clay to the welded end of the test sample, then heat the welded end of the test sample until the clay dries, and then apply a paste-like corrosive medium to the outer surface of the first test material in the test sample. Step S303: Place the test sample coated with the paste-like corrosive medium in the heating device, and then heat the test sample at a fixed heating rate until it reaches the target test temperature. After heating, stop heating, hold the sample at that temperature for a preset time, and then cool it to ambient temperature. Step S304: After repeating step S303 for the preset number of cycles, take out the test sample, clean the test sample, and then spray the penetrant.

[0015] Furthermore, step S300 also includes the following sub-steps: Step S305: Remove the penetrant from the surface of the test sample, and then spray the developer onto the surface of the test sample after the penetrant has dried. Step S306: Irradiate the surface of the test sample with ultraviolet light; If there is a fluorescent display area on the surface of the test sample, the corresponding fluorescent display area is determined to be a crack. At the same time, it is determined that the first test material has undergone high temperature stress corrosion cracking, the subsequent cyclic heating test is stopped, and the current number of cycles is recorded as the number of cycles for crack initiation of the test sample. If there is no fluorescent display area on the surface of the test sample, proceed to step S307; Step S307: Repeat the cyclic heating of the test sample until the maximum number of cycles is completed or cracks appear on the surface of the test sample, then stop the cyclic heating. If cracks appear on the surface of the test sample, it is determined that the first test material has undergone high-temperature stress corrosion cracking, and the corresponding number of cycles is recorded as the number of cycles initiation of cracks in the test sample. If no cracks are found on the surface of the test sample after the maximum number of cycles is completed, it is determined that the first test material did not undergo high-temperature stress corrosion cracking under the preset tensile stress.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention first sets the second plate thickness corresponding to the second test material in the high temperature stress corrosion test based on the material test data, and then anneales the test sample prepared by the first test material and the second test material, and determines whether there are defects in the annealed test sample, thereby achieving the pre-screening of the test sample to remove defects and improving the reliability of subsequent test data. 2. This invention uses the prepared synthetic coal ash to heat the test sample, and then judges whether the test sample has undergone high-temperature stress corrosion cracking after the heating test. This is beneficial for effectively reproducing and evaluating the corrosion cracking behavior of water-cooled wall pipes in real use environment. It also eliminates the need to rely on easily corroded and degraded high-temperature rigid fixtures when conducting high-temperature stress corrosion tests on water-cooled wall pipes under different stress states, thus avoiding the problem of stress loading distortion caused by fixture performance degradation. Attached Figure Description

[0017] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to the accompanying drawings.

[0018] Figure 1 This is a flowchart of the method of the present invention; Figure 2 These are the three views of the test sample in this invention; Figure 3 This is a flowchart of the high-temperature stress corrosion test in this invention; Figure 4 This is a schematic diagram of the electronic device in this invention. Detailed Implementation

[0019] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1, please refer to Figures 1-3 As shown, the technical solution provided by this invention is: a method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers. This method first calculates the second plate thickness of the second test material using the heating temperature difference in the high-temperature stress corrosion test and the difference in the linear expansion coefficients between the first and second test materials. Then, a test sample is constructed based on the first and second test materials, and the test sample is subjected to annealing and non-destructive testing. After the test sample passes the non-destructive testing, synthetic coal ash is prepared, and a paste-like corrosive medium is prepared using the synthetic coal ash and a test solution. The test sample is then subjected to a high-temperature stress corrosion test using the paste-like corrosive medium. Finally, it is determined whether the test sample experiences high-temperature stress corrosion cracking under a preset tensile stress. In this embodiment, the specific method for high-temperature stress corrosion testing of the water-cooled wall of the power plant boiler is as follows: Step S100: Set the second plate thickness corresponding to the second test material for the high-temperature stress corrosion test based on the material test data; In this embodiment, the first test material is specifically a low-alloy heat-resistant steel water-cooled wall pipe, and the second test material is specifically austenitic heat-resistant steel. The material test data specifically include the first linear expansion coefficient and first elastic modulus of the first test material at the target test temperature, and the second linear expansion coefficient and second elastic modulus of the second test material. For example, taking a high-temperature stress corrosion test where the temperature is heated from 20°C to 550°C, the first linear expansion coefficient of the first test material is 14.42 × 10⁻⁶. -6 / ℃, the second linear expansion coefficient of the second test material is 16.56×10 -6 / ℃; Elastic modulus is a physical quantity that represents a material's ability to resist elastic deformation; In this embodiment, step S100 includes the following sub-steps: Step S101: Obtain the target test temperature for the high-temperature stress corrosion test on the first test material, and simultaneously obtain the ambient temperature of the test environment for the first and second test materials. Subtract the ambient temperature from the target test temperature to calculate the heating temperature difference ΔT for the high-temperature stress corrosion test. Since the first and second test materials are welded together to form a whole and are heated simultaneously during the test, the two materials have the same target heating temperature. Therefore, only the target heating temperature of the first test material needs to be obtained. In practice, the ambient temperature is 20℃; since the first and second test materials need to be heated, the target test temperature is higher than the ambient temperature, and the calculation results do not need to be taken as absolute values; the ring ingot temperature is a fixed value, and the ambient temperature can be 20℃ in the actual experiment. Step S102: Obtain the first linear expansion coefficient of the first test material and the second linear expansion coefficient of the second test material; subtract the first linear expansion coefficient from the second linear expansion coefficient to calculate the difference Δa between the linear expansion coefficients of the first test material and the second test material. In this embodiment, taking a high-temperature stress corrosion test from 20℃ to 550℃ as an example, the difference in the coefficient of linear expansion is specifically 2.14 × 10⁻⁶. -6 / ℃; It should be noted that the difference in the coefficient of linear expansion is different when heated to different target test temperatures; Step S103: Obtain the first plate thickness t1 and the first elastic modulus E1 of the first test material, and the second elastic modulus E2 of the second test material; It should be specifically noted that, in order to avoid warping and deformation of the first and second test materials during the welding process, the thickness of the first plate is greater than or equal to three millimeters. In this embodiment, the thickness of the first plate is equal to three millimeters. When the thickness of the first plate is increased, the thickness of the second plate must be increased simultaneously. Step S104: Calculate the thickness t2 of the second plate based on the equilibrium equations of the first and second test materials during heating in the high-temperature stress corrosion test. The specific calculation process is as follows: During the heating process in the high-temperature stress corrosion test, the first and second test materials are in equilibrium and satisfy the equilibrium equation 2×E1×t1×(ε-a1×ΔT)+E2×t2×(ε-a2×ΔT)=0. The tensile stress of the first test material is derived from the equilibrium equation. The derivation process is as follows: The equilibrium equation is: 2×E1×t1×(ε-a1×ΔT)+E2×t2×(ε-a2×ΔT)=0, where ε is the common strain. This equation indicates that the axial forces generated by the two first test materials cancel each other out with the axial force generated by the second test material. The entire structure consisting of the first and second test materials has no external axial force. E1×t1×(ε-a1×ΔT) represents the axial force of the first test material at a fixed length. Expanding the equilibrium equation yields (2×E 1×t1+E2×t2)ε=(2×E1×t1×a1+E2×t2×a2)ΔT, therefore ε=[(2×E1×t1×a1+E2×t2×a2)ΔT] / (2×E1×t1+E2×t2;The tensile stress of the first test material is σ1=E1(ε-a1×ΔT). Substituting the common strain ε into the tensile stress σ1 of the first test material, we get σ1=(E1×E2×t2×Δa×ΔT) / (2×E1×t1+E2×t2). Substituting the preset tensile stress σi corresponding to the first test material in the high-temperature stress corrosion test into the tensile stress calculation formula, the second plate thickness t2 of the second test material is calculated. The specific calculation formula is as follows: t2 = (2 × E1 × t1 × σi) / [E2 × (E1 × Δa × ΔT - σi)]; where E1, E2, t1, σi and ΔT are all known values.

[0021] Step S200: Anneal the test sample prepared by the first test material and the second test material, and then determine whether there are defects in the annealed test sample. In this embodiment, step S200 includes the following sub-steps: Step S201, as follows Figure 2 As shown, two pieces of first test material with a thickness of one plate and one piece of second test material with a thickness of two plates are prepared. Specifically, in the actual test, the length of the effective test area in the top view can be 100 mm and the width can be 5 mm, the length of the welded end can be 10 mm and the width can be 20 mm, and the length of the rounded transition area can be 10 mm. The effective test area is specifically the effective area for high-temperature stress corrosion test. The welded end is specifically used to weld the first test material and the second test material. The rounded transition area is used to increase the distance between the welded end and the effective test area and reduce the impact of the welding process on the effective test area. Step S202: The first test material and the second test material are stacked and placed according to the fixed stacking method, and the first test material and the second test material are welded to obtain a test sample for high temperature stress corrosion test. Specifically, welding materials are used to weld the two ends of the first and second test materials; nickel-based welding materials are preferred as welding materials during the welding process to suppress carbon migration when the welding temperature is greater than or equal to 425°C; the fixed overlay method is to use the first test material as the outer layer material and the second test material as the middle material for overlay. Step S203: Heat the test sample to the annealing temperature and hold it at that temperature for a fixed time, then cool the test sample to the ambient temperature to obtain the annealed test sample. Specifically, step S203 is used to anneal the welded test specimen to eliminate residual welding stress generated during the welding process; the annealing temperature is less than or equal to the target test temperature. Step S204: Heat the test sample to the target test temperature using a heating device, maintain the temperature for a fixed time, and then cool the test sample to the ambient temperature. The heating device is specifically a muffle furnace; Step S205: Repeat step S204 a fixed number of times to cyclically heat the test sample, and then analyze and detect whether there are defects in the test sample using non-destructive testing methods. The specific testing process is as follows: First, the surface of the test sample is cleaned. Then, the ultrasonic probe is moved sequentially along the weld end - rounded corner transition area - effective test area - rounded corner transition area - weld end, and the amplitude of the ultrasonic signal detected by the ultrasonic probe is recorded. When the amplitude of any ultrasonic signal is greater than or equal to a preset threshold, it is determined that the test sample has a defect. Steps S201 to S204 are repeated to prepare the test sample again until the test sample has no defects, and then step S300 is entered. When the amplitude of all ultrasonic signals is less than the preset threshold, the test sample is deemed qualified and proceeds to step S300. The surface of the test sample can be cleaned using a stainless steel wire brush. Defects on the test sample can include welding defects such as cracks, lack of fusion, porosity, or slag inclusions, all of which can be detected and identified using an ultrasonic probe. The preset threshold is calibrated based on the equipment sensitivity and material characteristics. It should be noted that steps S204 and S205 are used to pre-inspect the test sample, screening out test samples with welding defects and those that fail to eliminate residual stress after welding, so as to avoid unqualified test samples interfering with the subsequent test results.

[0022] Step S300: The test sample is heated using the prepared synthetic coal ash, and then it is determined whether the test sample has undergone high-temperature stress corrosion cracking after the heating test is completed. In this embodiment, step S300 includes the following sub-steps: Step S301: Prepare synthetic coal ash according to the preset mass fraction of chemical reagents, and then drop the test solution into the synthetic coal ash to obtain a paste-like corrosive medium; In practice, the test solution is an anhydrous ethanol suspension; the preset mass fraction of chemical reagents in the synthetic coal ash can be adjusted according to experimental requirements, or the synthetic coal ash can be prepared based on a fixed preset mass fraction; the composition table corresponding to the fixed preset mass fraction is shown in Table 1: Step S302: Apply clay to the welded end of the test sample, then heat the welded end of the test sample until the clay dries, and then apply a paste-like corrosive medium to the outer surface of the first test material in the test sample. It should be specifically noted that the clay is high-temperature resistant clay. After the high-temperature resistant clay is coated on the welding end, it can isolate the welding end from the corrosive medium and avoid corrosion of the welding end, which would affect the accuracy of the test results. Step S303: Place the test sample coated with the paste-like corrosive medium in the heating device, and then heat the test sample at a fixed heating rate until it reaches the target test temperature. After heating, stop heating, keep it at the temperature for a preset time, and then cool the test sample to the ambient temperature. Specifically, the fixed heating rate can be five degrees Celsius per minute; the preset duration can be one hour; the cooling of the test sample specifically involves the test sample and the muffle furnace being allowed to cool naturally to ambient temperature. Step S304: After repeating step S303 for the preset number of cycles, take out the test sample, clean the test sample, and then spray the penetrant. The preset number of cycles can be ten; the penetrant is specifically a fluorescent penetrant, which is used to make the cracks on the surface of the test sample visible in color; Step S305: Remove the penetrant from the surface of the test sample, and then spray the developer onto the surface of the test sample after the penetrant has dried. Specifically, the developer is used to absorb and guide the penetrating liquid inside the cracks that have penetrated into the surface of the test sample to the surface of the test sample, so that the cracks on the surface of the test sample are clearly displayed. Step S306: Irradiate the surface of the test sample with ultraviolet light; If there is a fluorescent display area on the surface of the test sample, the corresponding fluorescent display area is determined to be a crack. At the same time, it is determined that the first test material has undergone high temperature stress corrosion cracking, the subsequent cyclic heating test is stopped, and the current number of cycles is recorded as the number of cycles for crack initiation of the test sample. If there is no fluorescent display area on the surface of the test sample, proceed to step S307; Step S307: Repeat the cyclic heating of the test sample until the maximum number of cycles is completed or cracks appear on the surface of the test sample, then stop the cyclic heating. If cracks appear on the surface of the test sample, it is determined that the first test material has undergone high-temperature stress corrosion cracking, and the corresponding number of cycles is recorded as the number of cycles initiation of cracks in the test sample. If no cracks are found on the surface of the test sample after the maximum number of cycles is completed, it is determined that the first test material did not undergo high-temperature stress corrosion cracking under the preset tensile stress.

[0023] Example 2: This embodiment of the invention also provides an electronic device for running the aforementioned high-temperature stress corrosion test method for water-cooled walls of power plant boilers; see also... Figure 4 The schematic diagram of an electronic device provided by the embodiment of the present invention shown above includes a memory and a processor. The memory is used to store one or more computer instructions, which are executed by the processor to realize the above-mentioned method for high-temperature stress corrosion testing of water-cooled walls of power plant boilers. Furthermore, Figure 4 The electronic device shown also includes a system bus and a communication interface, with the processor, communication interface, and memory connected via the communication bus; The memory may include high-speed random access memory (RAM) and may also include non-volatile memory, such as at least one disk storage device. Communication between this system network element and at least one other network element is achieved through at least one communication interface (which can be wired or wireless), such as the Internet, wide area network, local area network, metropolitan area network, etc. The system bus can be an ISA bus, PCI bus, or EISA bus, etc. The system bus can be divided into address bus, data bus, control bus, etc. For ease of representation, Figure 4 The symbol is represented by only one bidirectional arrow, but this does not mean that there is only one communication bus or one type of system bus. The processor may be an integrated circuit chip with signal processing capabilities. In implementation, the steps of the above methods can be completed by integrated logic circuits in the processor's hardware or by software instructions. The processor can be a general-purpose processor, including a Central Processing Unit (CPU), a Network Processor (NP), etc.; it can also be a Digital Signal Processor (DSP), an Application Specific Integrated Circuit (ASIC), a Field-Programmable Gate Array (FPGA), or other programmable logic devices, discrete gate or transistor logic devices, or discrete hardware components. It can implement or execute the methods, steps, and logic block diagrams disclosed in the embodiments of this invention. The general-purpose processor can be a microprocessor or any conventional processor. The steps of the methods disclosed in the embodiments of this invention can be directly embodied in the execution of a hardware decoding processor, or executed by a combination of hardware and software modules in the decoding processor. The software modules can reside in random access memory, flash memory, read-only memory, programmable read-only memory, electrically erasable programmable memory, registers, or other mature storage media in the art. The storage medium is located in the memory, and the processor reads the information in the memory and, in conjunction with its hardware, completes the steps of the method described in the foregoing embodiments.

[0024] In embodiment three, the present invention also provides a computer storage medium storing computer-executable instructions. When the computer-executable instructions are called and executed by a processor, the computer-executable instructions cause the processor to implement the above-mentioned method for high-temperature stress corrosion testing of water-cooled walls of power plant boilers. For specific implementation, please refer to the method embodiment, which will not be repeated here. The computer program product for a high-temperature stress corrosion test method for water-cooled walls of power plant boilers provided in this embodiment of the invention includes a computer storage medium storing program code. The instructions included in the program code can be used to execute the methods in the preceding method embodiments. For specific implementation, please refer to the method embodiments, which will not be repeated here.

[0025] Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working process of the system and / or device described above can be referred to the corresponding process in the foregoing method embodiments, and will not be repeated here.

[0026] Furthermore, in the description of the embodiments of the present invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in the present invention based on the specific circumstances.

[0027] If the aforementioned functions are implemented as software functional units and sold or used as independent products, they can be stored in a computer-readable storage medium. Based on this understanding, the technical solution of this invention, essentially, or the part that contributes to the prior art, or a portion of the technical solution, can be embodied in the form of a software product. This computer software product is stored in a storage medium and includes several instructions to cause a computer device (which may be a personal computer, server, or network device, etc.) to execute all or part of the steps of the methods described in the various embodiments of this invention. The aforementioned storage medium includes various media capable of storing program code, such as USB flash drives, portable hard drives, read-only memory (ROM), random access memory (RAM), magnetic disks, or optical disks.

[0028] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for testing high-temperature stress corrosion of water-cooled walls in power plant boilers, characterized in that, The methods include: Step S100: Set the second plate thickness corresponding to the second test material for the high-temperature stress corrosion test based on the material test data; Step S200: Anneal the test sample prepared by the first test material and the second test material, and then determine whether there are defects in the annealed test sample. In step S300, the test sample is heated using the prepared synthetic coal ash, and then it is determined whether the test sample has undergone high-temperature stress corrosion cracking after the heating test.

2. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 1, characterized in that, The first test material was low-alloy heat-resistant steel water-cooled wall pipe, and the second test material was austenitic heat-resistant steel.

3. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 1, characterized in that, The material test data are the first linear expansion coefficient and first elastic modulus of the first test material at the target test temperature, and the second linear expansion coefficient and second elastic modulus of the second test material.

4. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 1, characterized in that, Step S100 includes the following sub-steps: Step S101: Obtain the target test temperature for the high-temperature stress corrosion test on the first test material, and at the same time obtain the ambient temperature of the test environment of the first test material and the second test material. Subtract the ambient temperature from the target test temperature to calculate the heating temperature difference of the high-temperature stress corrosion test. Step S102: Obtain the first linear expansion coefficient of the first test material and the second linear expansion coefficient of the second test material; subtract the first linear expansion coefficient from the second linear expansion coefficient to calculate the difference in linear expansion coefficients between the first test material and the second test material. Step S103: Obtain the first plate thickness and first elastic modulus of the first test material, and the second elastic modulus of the second test material; Step S104: Calculate the thickness of the second plate based on the equilibrium equation of the first and second test materials during heating in the high-temperature stress corrosion test.

5. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 4, characterized in that, The calculation process for the second plate thickness is as follows: During the heating process in the high-temperature stress corrosion test, the first test material and the second test material are in equilibrium and satisfy the equilibrium equation. The tensile stress of the first test material is derived based on the equilibrium equation. The second plate thickness of the second test material is calculated by substituting the preset tensile stress corresponding to the first test material in the high-temperature stress corrosion test into the tensile stress calculation formula.

6. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 1, characterized in that, Step S200 includes the following sub-steps: Step S201: Prepare two pieces of first test material with a first plate thickness and one piece of second test material with a second plate thickness; Step S202: The first test material and the second test material are stacked and placed according to the fixed stacking method, and the first test material and the second test material are welded to obtain a test sample for high temperature stress corrosion test. Step S203: Heat the test sample to the annealing temperature and hold it at that temperature for a fixed time, then cool the test sample to the ambient temperature to obtain the annealed test sample.

7. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 6, characterized in that, Step S200 further includes the following sub-steps: Step S204: Heat the test sample to the target test temperature using a heating device, maintain the temperature for a fixed time, and then cool the test sample to the ambient temperature. Step S205: Repeat step S204 a fixed number of times to cycle-heat the test sample, and then analyze and detect whether there are defects in the test sample, and obtain the ultrasonic signal amplitude. When the amplitude of any ultrasonic signal is greater than or equal to a preset threshold, it is determined that the test sample has a defect. Steps S201 to S204 are repeated to prepare the test sample again until the test sample has no defects, then proceed to step S300. When the amplitude of all ultrasonic signals is less than the preset threshold, the test sample is deemed qualified and proceeds to step S300.

8. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 7, characterized in that, The specific process for detecting the amplitude of the ultrasonic signal is as follows: Clean the surface of the test sample; Move the ultrasonic probe sequentially along the weld end - rounded corner transition area - effective test area - rounded corner transition area - weld end; Record the amplitude of the ultrasonic signal obtained by the ultrasonic probe.

9. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 7, characterized in that, Step S300 includes the following sub-steps: Step S301: Prepare synthetic coal ash according to the preset mass fraction of chemical reagents, and then drop the test solution into the synthetic coal ash to obtain a paste-like corrosive medium; Step S302: Apply clay to the welded end of the test sample, then heat the welded end of the test sample until the clay dries, and then apply a paste-like corrosive medium to the outer surface of the first test material in the test sample. Step S303: Place the test sample coated with the paste-like corrosive medium in the heating device, and then heat the test sample at a fixed heating rate until it reaches the target test temperature. After heating, stop heating, hold the sample at that temperature for a preset time, and then cool it to ambient temperature. Step S304: After repeating step S303 for the preset number of cycles, take out the test sample, clean the test sample, and then spray the penetrant.

10. The method for high-temperature stress corrosion testing of water-cooled walls in power plant boilers according to claim 9, characterized in that, Step S300 further includes the following sub-steps: Step S305: Remove the penetrant from the surface of the test sample, and then spray the developer onto the surface of the test sample after the penetrant has dried. Step S306: Irradiate the surface of the test sample with ultraviolet light; If there is a fluorescent display area on the surface of the test sample, the corresponding fluorescent display area is determined to be a crack. At the same time, it is determined that the first test material has undergone high temperature stress corrosion cracking, the subsequent cyclic heating test is stopped, and the current number of cycles is recorded as the number of cycles for crack initiation of the test sample. If there is no fluorescent display area on the surface of the test sample, proceed to step S307; Step S307: Repeat the cyclic heating of the test sample until the maximum number of cycles is completed or cracks appear on the surface of the test sample, then stop the cyclic heating. If cracks appear on the surface of the test sample, it is determined that the first test material has undergone high-temperature stress corrosion cracking, and the corresponding number of cycles is recorded as the number of cycles initiation of cracks in the test sample. If no cracks are found on the surface of the test sample after the maximum number of cycles is completed, it is determined that the first test material did not undergo high-temperature stress corrosion cracking under the preset tensile stress.